Correlation Between Climate Indicators and COVID-19 Pandemic in Nigeria, Ghana, and South Africa - Bakare-Aremu, Tunde Abubakar; Ibrahim , Kekere Sule; Baba-Umar, Saadatu; Mamman, Rakiya (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study examines the relationship between climatic indicators (maximum temperature, minimum temperature, precipitation, and relative humidity) and the spread of COVID-19 using weekly data of confirmed cases and death rates from 3/25/2020 to 12/30/2020 for Nigeria, South Africa, and Ghana. Using an ex-post research design and descriptive method of analysis, the results of the study confirm evidence of correlation between climatic variables and the spread of the COVID-19 virus among the three selected countries. However, the policy recommendation that emanates from this study is that climate mitigation policies can be promoted as pandemic prevention policies, thus making a stronger case for their implementation to forestall future reoccurrence.